FACTORS THAT REDUCE THE RISK OF EMOTIONAL BURNOUT IN MEDICAL STUDENTS - Поддубная, Антонина; Гончарук, Людмила; Андрущак, Маргарита; Корнивский, Богдан; Давыдюк, Арсен; Маковийчук, Кристина (SWorldJournal, 2022)
Abstract: Constant communication with patients and their relatives, being in a circle of complex human problems, negative emotions of fear, pain, as well as a sense of responsibility for life and recovery of patients, high competence and continuous profes